THE INFLUENCE OF THE OCCUPATIONAL SAFETY AND HEALTH (K3) MANAGEMENT SYSTEM ON EMPLOYEE PERFORMANCE AT PT UPC. BAYU ENERGY SIDRAP DISTRICT SIDRAP - Refaldi, Muhammad; Jam’an, Andi; Hidayat, M. (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to determine the influence of the Occupational Safety and Health (K3) Management System on Employee Performance at PT.UPC Sidrap Bayu Energi, Sidrap Regency. The population in this study were all employees of PT.UPC Sidrap Bayu Energi, Sidrap Regency, totaling 34 employees. The type of research used is descriptive quantitative. The data sources used are primary data sources, namely information originating from observations and questionnaires. Secondary data sources are data sources obtained from documentation or literature study. The data analysis technique used is Simple Regression Analysis using statistical calculations using the Statistical Package for the Social Science (SPSS) version 26 application.The research results show that the Occupational Safety and Health Management System (K3) (X) has a positive and significant effect on employee performance (Y). the results of this research t value > t table (9,148 > 1.691) and the significant value = 0.00 ˂ 0, 05